Governance and City Regeneration - a New Methodological Approach for Design and Evaluation - Neto, Paulo (2011)
New forms of governance targeting urban competitiveness are increasingly oriented to vertical (between lower and high levels of government and cooperation forms between entities and firms along the production chain) and horizontal (between firms or different municipalities or public and private entities) cooperation (OEDC, 2005). The main purpose of this paper is to propose a new methodology for territorial analysis and planning focused on urban regeneration processes and its governance mechanisms. A new methodology that seeks, for each specific urban context, contribute to the following results: i) Help select the most appropriate governance model to be adopted for each process of urban regeneration; ii) Monitor the partnership process and help promote the partnership guidance; iii) Support the design process and the definition of the strategic approach and projects; iv) Monitor the process of implementing the strategy and support multidimensional and multiscale evaluation of its results; v) Evaluate the socio-economic and territorial impacts of urban regeneration processes.